Analisis Pengaruh Pendidikan dan Jumlah Penduduk Terhadap Ketersediaan Lapangan Pekerjaan di Provinsi Sumatera Utara - Hasibuan, Ahmad Muniruddin; Nasution, Muhammad Lathief Ilhamy; Silalahi, Purnama Ramadani (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to analyze the influence of education and population on the availability of jobs in North Sumatra. Methodology: The methods used are qualitative and quantitative methods (combined/mixed methods). The data used by researchers in this paper are primary data (interviews) and secondary data obtained from the BPS (Central Statistics Agency) of North Sumatra, the government or other agencies, articles, news or websites that can support this research and the qualitative method uses an interview system with sources related to the problems studied. Results: The results of this study indicate that the education variable has a t-value of 2.994> t table = 1.943 so it can be concluded that education has a significant positive effect on the availability of jobs while the population has a t-value of 1.827 <t table = 1.943 so it can be concluded that the population variable not effect on the availability of jobs in the province of North Sumatra. Limitations: The results of the interview are that the availability of jobs will be easily obtained by job seekers if they have work skills, higher education and previous work experience. Contribution: The result have been salutation about how analysis project about education given solution for student.